Efektivitas Pengelolaan Sampah Oleh Dinas Kebersihan Dan Pertamanan Kota Manado - Salinding, Rezky Amelia; POSUMAH, JOHNNY HANNY; Palar, Novie Anders (Sam Ratulangi University, 2016)
ABSTRACT : With the increasing population and the activities of the community in the city of manado, alsoincreased the amount of the more then the volume of trash in the produce. This is affecting the conditionsof the LANDFILL at the moment. Waste management is the collection, transport, processing, recycling, ordisposal of waste material. Waste management is very important in order not to bad on the community and theenvironment. The purpose of this study was to determine whether waste management by the cleanliness andLandscaping Manado city is already effective. Data collection techniques in research is through: directobservation to observation i.e location research, conduct interview and documentation.The research method used was qualitative research methods. The method of this research aims to know theeffectiveness of waste management by the cleanliness and Landscaping of the city of Manado. As for whobecomes the respondents in this study was the Secretary of the Department and staff officers of the Departmentof hygiene and Landscaping of the city of Manado and involving the community of the city of Manado.Based on the research that has been done then the effectiveness of waste management by cleanlinessand Landscaping of the city of Manado city is still not effective because there are still many obstacles in the face.The government should give full attention towards waste management, especially in the areaof detention that kecamatan bersehati market volume of trash.For it can be inferred that in the effectiveness of waste management in the service of cleanlinessand Landscaping Manado was ineffective because of the criteria,namely production, efficiency,satisfaction,adaptation/customisation, developmentand no one is fulfilled.Key Words: Effectiveness, Waste Management